Risks of Lithium Ore Mining and Their Mitigation - Jovanović, Saša; Popović, Ognjen; Čolović, Miloš; Tomović, Milica; Tarić, Mirsad; Majstorović, Miroslav (Napredak, 2024)
Lithium is a key mineral for modern technology and the global energy transition. Its use in batteries for electric vehicles, smart devices, and renewable energy storage systems makes it an indispensable resource. However, the extraction process poses significant risks to the environment, local communities, and worker health. Water consumption, land degradation, pollution, and displacement of populations are among the most common challenges. The Jadar Project in Serbia represents a potential positive example of sustainable mining practices. This paper analyses the main risks and mitigation measures, including technological innovations, land reclamation, and community involvement.
Keywords: lithium; mining; mitigation measures; reclamation; environmental risks